The impact of State of Surrender on the relationship between engagement in substance use treatment and meaning in life presence: a pilot study - Sease, Thomas B.; Cox, Cathy R.; Wiese, Amanda L.; Sandoz, Emily K.; Knight, Kevin (Frontiers in Psychology, 2024)
The current study examined the construct of State of Surrender (SoS)—defined as a willingness to accept, without resistance, what is to come—and investigated SoS as a statistical mediator of the relationship between engagement in substance use treatment and meaning in life (MIL). Using a cross-sectional design, participants were 123 people involved with the legal system participating in a 6-month residential treatment program for substance use. Results showed that measures of treatment engagement, including treatment participation, counselor rapport, and peer support, were all positively associated with SoS scores (R2s ≥ 21.16). Moreover, while controlling for time spent in treatment, SoS statistically mediated the positive association between aspects of treatment engagement and MIL. State of Surrender may be a targetable process in substance use treatment that aids in recovery by orienting clients toward what they find meaningful in life. Future directions and practical considerations are discussed.